ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PEGAWAI KANTOR CAMAT TIGANDERKET KABUPATEN KARO - Ingan Ukur Br Sitepu; Menanti Sembiring (JURNAL REGIONOMIC, 2020)
This research was conducted to find out and analyze the factors that affect job satisfaction, employees of the Tiganderket Sub-District Head office in Karo District. In this study, the population was 32 employees of the Tiganderket sub-district office in Karo District. The population and sample in this study were all employees of the Tiganderket Sub-District Office of Karo Regency, amounting to 32 respondents. To see the factors that affect the job satisfaction of Tiganderket sub-district office employees, four indicators are the measure of work, colleagues, leadership, career planning, data collection methods in this studied using the questionnaire method. The instruments that were compiled were then tested for validity using statistical formulas. The analysis uses descriptive percentages and multiple regression analysis which have been tested beforehand with the classic assumption test in the form of normality, multicollinearity, and heteroscedasticity. Based on the results of multiple regression analysis the equation is Y = 4.094 + 0.323 X1 + 0.335 X2 + 0.202 X3 + 0.021 X4 + e. Test the significance of the regression equation using the F test, based on the calculation results obtained Fcount = 13.662 with a probability of 0,000 <0.05. The magnitude of the effect of work, coworkers, leadership, and career planning on job satisfaction simultaneously was 59.1%. The results of the study conclusions, in general, the factors that affect job satisfaction at the Tiganderket Sub-District Office of Karo District, there are effects of work, colleagues, leadership, and career planning on job satisfaction simultaneously while partially not all variables affect job satisfaction. Suggestions that can be given are that agencies should continue to explore the potential of their employees and improve performance standards.